SENSORY ACCOMMODATION AS A RESOURCE FOR POST-LIVER TRANSPLANT SUPPORT IN EARLY CHILDHOOD (REMUNOM, 2024)
Liver transplantation is a major and complex surgical intervention with a high risk of fluid and blood loss, as the liver is closely related to the blood coagulation mechanism. Objective: To map the care strategies of the occupational therapist in assisting a pediatric patient who presented sensory dysfunction due to a liver transplant performed in October 2023. Method: This is a case study conducted with a post-liver transplant child who exhibited psychomotor agitation, rejection of social contact, and a continuous craving for physical touch from the father, which compromised hospital safety. A research release request was sent to the parents and the institution. This study was approved by the Research Ethics Committee under protocol number 6609833. Results: The occupational therapist, using the Sensory Integration approach, aimed to prevent these behaviors by promoting emotional regulation and adaptation to the hospital environment. Sensory resources were individualized and accompanied by daily caregiver guidance, resulting in improved social interaction, better control of psychomotor agitation, and enhanced hospital safety. This highlights the importance of this professional’s role in complex pediatric rehabilitation contexts post-transplant. Conclusion: This intervention proved effective in promoting emotional regulation, adapting to the hospital environment, and improving the child’s social interaction in complex contexts. The individualization of sensory resources, combined with daily caregiver support, contributed to the control of psychomotor agitation and hospital safety. These results underscore the relevance of occupational therapists in developing and implementing strategies that address each child's specific needs, promoting well-being and facilitating the rehabilitation process. Continued research is recommended to further explore the contributions of Sensory Integration in high-complexity pediatric scenarios